Fabrication and laser properties of transparent Yb:YAG ceramics - Luo, Dewei (2013)
High optical quality transparent Yb:YAG laser ceramics have been successfully fabricated by a vacuum reactive sintering method. Commercial Al2O3 powder and co-precipitated Y2O3 and Yb2O3 powders were used as the raw materials. In-line transmittances at 1300 nm and 400 nm were measured to be 83.6% and 81.8% respectively for a 3 mm thick mirror polished Yb:YAG ceramics sample. Continuous wave (CW) lasing at the wavelength of 1030 nm was achieved when pumped by a 940 nm fiber coupled laser diode. A slope efficiency as high as 62.7% was obtained.